Implementasi Kebijakan Strategi Kepala Sekolah dalam Meningkatkan Mutu Pendidikan - Ida Suryani (Jurnal Gentala Pendidikan Dasar, 2021)
The headmaster as a leader has considerable responsibility for the development and progress of the school. This research describes the improvement of school quality, the principal's strategy for improving education quality. The development and progress of the school can be seen from the performance of the school headmaster and the headmaster is able to utilize the resources effectively and efficiently. As well as seeing and the task of the headmaster faced with the challenge to implement a planned and continuously organized education in developing the quality of education. The study used a qualitative approach with descriptive design and case study type. The research results include: (1) The school principal's strategy in improving the quality of education is the fulfillment of school infrastructure, professionalism of teachers, (2) implementation of the Program to improve the quality of education in schools, (3) evaluation to improve the quality of education in schools, (4) Constraints faced by schools that are problems funding the school Program.